Psychometric properties of behavioural regulation in exercise questionnaire-4 in Chinese adolescents - Xu, Zhongliang; Shamsulariffin, Samsudin; Azhar, Yaacob; Xi, Mizhe (Taylor and Francis Group, 2024)
This study aims to determine the psychometric properties of the Chinese version of the Behavioural Regulation in Exercise Questionnaire-4 (C-BREQ-4) within the context of the adolescent population in China. A total of 846 Chinese adolescents (389 males and 457 females, comprising 411 secondary school students and 435 high school students), aged 12-18, with a mean (x̅) age of 14.67 (±1.45) years, participated in this study. The C-BREQ-4 was tested for convergent, discriminant, structural and criterion validity, internal consistency reliability, and cross-gender and grade invariance. Confirmatory factor analysis (CFA) revealed that the measurement model of the C-BREQ-4 with seven factors and 26 items had a good data fit. The 7-factor, 26-item C-BREQ-4 had good discriminant and convergent validity and internal consistency reliability. The correlation between the factors moderated by different motives supports the quasi-unitary model hypothesised by SDT, which provides support for the structural validity of the C-BREQ-4. Different association patterns were found between different motivational regulations and behavioural outcomes (physical activity; PA), a result that provides support for the criterion validity of the 7-factor, 26-item C-BREQ-4. Multi-group CFA showed evidence favouring the 7-factor, 26-item C-BREQ-4 remaining consistent across gender and grade levels. The C-BREQ-4 is a useful and robust measurement tool for assessing 7-factor motivational regulation in a Chinese adolescent population, adding evidence to the cross-cultural applicability of the BREQ-4. Furthermore, it can be used to better understand different types of motivational regulation in adolescent populations.